A Field Study of Knowledge Workers' Use of Interactive Horizontal Displays - Morris, Meredith Ringel; Brush, A.J.; Meyers, Brian (Proceedings of IEEE Tabletops and Interactive Surfaces 2008, 2008)
To better understand the potential for horizontal surfaces in day-to-day work, we conducted a field study. We collected and analyzed over a month of use data from eight participants who used horizontal displays in conjunction with their existing office computer setups. Our analysis of the system logs, observations, and interview data from the study reveals clear differences in preference and use patterns for horizontal and vertical display configurations. Based on these findings, we formulate hardware and software design guidelines that would increase the utility of interactive horizontal displays for office scenarios.